E-moderating: the key to teaching and learning online - Salmon, Gilly
If you are a e-teaching or you are in the e-learning business, you must buy and read this book. This book explain the e-teaching work, how to moderate a online class without lose the control, how to train and monitoring a e-moderator,... talk about the important things in the success of the work of a e-teacher/e-moderator. I found this book very informative, I recomend it